Chemical composition and sensory properties of Caulerpa racemosa seaweed yellow noodle - Ahmad, Aziani; Zainol, Zamzila; Abdul Haiyee, Zaibunnisa; Mohd Nor, Norakma; Nazihah Mohamad Nizam, Nazatul; ., . (International Journal of Engineering and Technology, 2018)
Chemical composition and sensory properties of the dried Caulerpa racemosa collected from Port Dickson were determined. Addition of Caulerpa racemosa as an ingredient will enhance the nutritional composition of yellow noodle. In this study, the wheat flour that was used for the preparation of the noodles was partially substituted with the 20 g, 40 g and 60 g dried Caulerpa racemosa powder. The addition of Caulerpa racemosa powder in noodle increase the lipid and ash contents significantly (p<0.05). The lipid content was range from 2.24% d.w. to 8.2% d.w. The ash content was from 0.14% d.w. to 1.7% d.w. However, there were no significant different between original noodle and Caulerpa racemosa noodles in terms of moisture and protein contents. Noodle with addition of 20 g Caulerpa racemosa has mild seaweed flavour, aromatic odor, have a soapy texture, attractive appearance and acceptable sensory. All the sensory parameters scored higher than 5, which mean the average acceptance of noodle with 20 g of Caulerpa racemosa is good. Therefore, the noodle with 20 g seaweed replacement is recommended to be applied for nutritional and taste enhancement.Â Â